Advanced Lipidomics in the Modern Meat Industry: Quality Traceability, Processing Requirement, and Health Concerns - Li, Chengliang; Ozturk-Kerimoglu, Burcu; He, Lichao; Zhang, Min; Pan, Jiajing; Liu, Yuanyi; Zhang, Yan; Huang, Shanfeng; Wu, Yue; Jin, Guofeng (Frontiers in Nutrition, 2022)
Over the latest decade, lipidomics has been extensively developed to give robust strength to the qualitative and quantitative information of lipid molecules derived from the physiological animal tissues and edible muscle foods. The main lipidomics analytical platforms include mass spectrometry (MS) and nuclear magnetic resonance (NMR), where MS-based approaches (e.g., ‘shotgun lipidomics’, ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS), matrix-assisted laser desorption and ionization time-of-flight mass spectrometry (MALDI-TOF-MS)) have been widely used due to their good sensitivity, high availability and accuracy in identification/quantification of basal lipid profiles in complex biological point of view. However, each method has the limitations for lipid-species (e.g., fatty acids, triglycerides, phospholipids) analysis, and thereby requires the extending of effective chemometric-resolved modelling and novel bioinformatic strategies towards the molecular insights into alterations in the metabolic pathway. This review summarized the latest research advances regarding the application of advanced lipidomics in muscle origin and meat processing. We concisely highlighted and presented how the biosynthesis and decomposition of muscle-derived lipid molecules can be tailored by intrinsic characteristics during meat production (i.e., muscle type, breed, feeding, freshness). Meanwhile, the consequences of some crucial hurdle techniques from both thermal/non-thermal perspectives were also discussed as well as the role of salting/fermentation behaviours in postmortem lipid biotransformation. Finally, we proposed the inter-relationship between potential/putative lipid biomarkers of representative physiological muscle and processed meats, their metabolism accessibility, general nutritional uptake, and potency on human health.